2017
DOI: 10.1111/itor.12475
|View full text |Cite
|
Sign up to set email alerts
|

A min–max solution to optimise planned lead time in a remanufacturing system

Abstract: Determining a rational planned lead time (PLT) is a critical and difficult problem in production planning, especially for a remanufacturing system. This paper considers an optimisation problem of the PLT in a make‐to‐order remanufacturing system to coordinate disassembly–remanufacturing–reassembly and to improve performance. This optimisation model is designed to determine the PLT that minimises the inventory holding and shortage costs. Given the unknown distribution of remanufacturing time but with known firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Liu et al. (2019) scheduled the lead times of cores for RPs to coordinate disassembly, remanufacturing, and reassembly for a remanufacturing system, allowing stockout. Liao and Li (2021) studied the optimal order quantity of FGs in a closed‐loop supply chain by extending the classical economic order quantity model to the case of random market demand.…”
Section: Literature Review and Research Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al. (2019) scheduled the lead times of cores for RPs to coordinate disassembly, remanufacturing, and reassembly for a remanufacturing system, allowing stockout. Liao and Li (2021) studied the optimal order quantity of FGs in a closed‐loop supply chain by extending the classical economic order quantity model to the case of random market demand.…”
Section: Literature Review and Research Gapsmentioning
confidence: 99%
“…The earliest work can be traced to Goyal (1976), in which a joint economic lot-sizing model was developed for a twoechelon supply chain, but this work does not involve remanufacturing. Recently, production and inventory management has been extended to the field of remanufacturing (e.g., Mawandiya et al, 2017;Liu et al, 2019). Mawandiya et al (2017) considered a remanufacturing system that consists of a manufacturer, a remanufacturer, and a retailer and cores of the same quality.…”
Section: Inventory Management With Remanufacturingmentioning
confidence: 99%
“…Liu et al. (2019a) discuss the production planning for a remanufacturing system and set the planned lead time. Esenduran et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Cui et al (2015) show that the improvement in the mean square forecast error for all studied products ranged from 7.1 to 81.1% if the company included the retailer’s sales data into the demand forecast based on the data collected from a consumer packaging company. In recent years, remanufacturing of closed-loop supply chains (CLSCs) has made a dent in industry and academia due to the scarcity of material resources ( Govindana et al, 2015 ; Liu B. Y. et al, 2019 ; Aminipour et al, 2021 ; Qiao and Su, 2021 ; Soleimani et al, 2021 ; Zhang and Zhang, 2022 ). Although many studies have shown that remanufacturing can reduce production costs by 40–65%, Akçalı and Çetinkaya (2011) argue that compared to the traditional supply chain, the coordination problem is more sophisticated due to the uncertainty of the recycle rate and market demand in the CLSC.…”
Section: Introductionmentioning
confidence: 99%